Banana consumption patterns in the guayaquileño market - Salazar Soledispa., Vicente; Martillo Mieles., Oswaldo; Duran Salazar., Galo (Revista Universidad de Guayaquil, 2017)
This paper aims to establish patterns of behavior in banana consumption of Guayaquil, a survey was conducted to 384 people in a population of 2, 350.915 inhabitants of the city Guayaquil at the last census of 2010 INEC, 201 males and 183 women of different ages and socio-economic level. The sample was obtained with an estimation error of 5% and 95% confidence, 50% of success. Different variables banana consumption (weekly consumption units, place of purchase, preferably Rankin, purchase frequency) and demographic variables (age, gender, purchase motivation, socioeconomic status) were analyzed. Key findings indicate that 77.34% of the sample did not know the nutritional benefits of bananas and that 68% of the sample purchase bananas from personal taste and preferably in the truck. Guayaquileans have changed their pattern of consumption of fruit, prefer imported to national.
Keywords: patterns; banana; consumption; market; Guayaquil